Letter from Harold Monro to Herbert Read, June 26, 1930 - http://id.worldcat.org/fast/919 (1930)
A letter to Sir Herbert Read from Harold Monro, poet, publisher, editor, and owner of The Poetry Bookshop, in which a disgruntled Monro reflects on a meeting with the 'Criterion Club' the evening before.